PENENTUAN KONDISI INTERESTERIFIKASI KIMIAWI UNTUK SINTESIS LEMAK MARGARIN DARI MINYAK WIJEN DAN PALM STEARIN - , ASRI PUSPITA W. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Interesterification is one of the processes used to modify the physicochemical characteristics of oils and fats. Chemical interesterification involves a randomization exchange of acyl groups in triacyglycerol by using chemical catalysts. The aim of this study was to determine optimum conditions of chemical interesterification between Sesame Oil (SO) and Palm Stearin (PS) using sodium methoxide as chemical catalyst that produce margarine fats which had slip melting point at body temperature. This study also evaluated the effect of chemical interesterification to antioxidant activity and antioxidant compounds in margarine fats. Ratio between SO and PS used as dependent variable. Time and temperature of chemical interesterification was optimized using Central Composite Design (CCD) Response Surface Methodology (RSM). The response was Slip Melting Point (SMP) which targeted at 36-37ËC (body temperature). Chemical interesterification caused rearrangement of triacylglycerol species, resulting in lowering SMP, decreasing antioxidant activity and antioxidant compounds in interesterified blends. Correlations between SMP (Y), with time (A) and temperature (B) of chemical interesterification shows in linear equation: Y = 51,2 â 0,12 A â 0,10 B. Desirable margarine fats containing SO and PS with ratio 50:50 (w/w) were obtained at optimum time 60 minutes, and optimum temperature 70ËC using 0,5% (w/w) sodium methoxide. This optimum conditions produce margarine fats with SMP 37,17ËC that suited to application as baking/confectionary fats. From the evaluation of antioxidant compounds, margarine fats present 24,5% of total antioxidant, 2.76 x 10-4% of total carotene, 3.54 x 10-3 mg galic acid/kg of total phenolic content, and 887 ppm of sesamin that might be considered for possible health benefits.